Interdiscursividade em um Projeto Político-Pedagógico - Silva, Carmem Lúcia da (2009)
Taking as theoretical basis, French Discourse Analysis, it will be emphasized that the pedagogic political project (PPP) from a Letters Undergraduation has been elaborated from tensive dialogues established among subjects inscribed in groups and social classes. They have been constituted through verbal interactions, in historic contexts. As such subjects are constructed by an interdiscursive exteriority, materialized in speeches, the PPP is a discursivity constituted by such exteriority, this variety of discourses, that is to say, by interdiscourse (already-said). As this research is a qualitative, analytic and interpretative one, it is searched to describe, interpret and analyze such other discourses which cross PPP, what provides a survey of some interdiscursive manifestations which compose this PPP. It is discussed concepts which underlie PPP, concerning the function of university, and Letters Undergradutation, aiming at showing which treatment is given to knowledge and which is professional academic formation and politics for students. It was put for reflection the hypothesis that in such PPP, there is an interpretation which dislocates some law meanings for teacher formation courses. It was searched to answer research questions: which discourses constitute such PPP? What are students functions in society, from the view of this PPP? What is the conception, expressed in PPP, concerning the role of university and knowledge forming language professionals? This research reflects on Letters Undergraduation, concerning teachers formation.